What are the impacts of alcohol supply reduction measures on police-recorded adult domestic and family violence in the Northern Territory of Australia? - Clifford, S.; Wright, C.J.C.; Miller, Peter; Coomber, K.; Griffiths, K.E.; Smith, J.A.; Livingston, Michael (WILEY, 2024)
Background: During 2017-18, the Northern Territory (NT) introduced a Banned Drinker Register (BDR) and Minimum Unit Price (MUP) NT-wide; Police Auxiliary Liquor Inspectors (PALIs) in three regional towns; and restrictions on daily purchases/opening hours (DPOH) in one regional town. The BDR is an individual-level alcohol ban; MUP is a pricing policy; and PALIs enforce bans on restricted areas at takeaway outlets. This study examines the impact of these policies on adult domestic and family violence (DFV). Methods: We examined DFV assaults and breaches of violence orders from January 2014 – February 2020 using interrupted time series models for NT, Greater Darwin, Katherine, Tennant Creek, and Alice Springs. To account for increasing numbers of individuals on the BDR we tested two timepoints (Sept 2017, March 2018). Findings: Following DPOH, assaults (78 %) and alcohol-involved assaults (92 %) decreased in Tennant Creek. After PALIs, assaults (79 %) in Tennant Creek, and breaches (39 %) and alcohol-involved breaches (58 %) in Katherine decreased. After MUP, assaults (11 %), alcohol-involved assaults (21 %) and alcohol-involved breaches (21%) decreased NT wide. After MUP/PALIs in Alice Springs, alcohol-involved assaults (33 %), breaches (42 %), and alcohol-involved breaches (57 %) decreased. BDR (Sept 2017) found increases in assaults (44 %) and alcohol-involved assaults (39 %) in Katherine and assaults (10%) and alcohol-involved assaults NT-wide (17 %). There were increases of 21 %-45 % in breaches NT-wide, in Darwin, Katherine, and Alice Springs. Following March 2018 found increases in assaults (33 %) and alcohol-involved assaults (48 %) in Katherine. There were increases - from 20 % to 56 % - in breaches in NT-wide, Katherine, and Alice Springs. Conclusion: PALIs and DPOH were associated with some reductions in DFV; the BDR was associated with some increases. The upward trend commences prior to the BDR, so it is also plausible that the BDR had no effect on DFV outcomes. Although MUP was associated with reductions in the NT-wide model, there were no changes in sites without cooccurring PALIs.